The Effect of Sleep Hours on Student Learning Achievement - Riko Alamsyah, Izzatun Nisa Amalia, Eko Wahyu Utomo (GLOBAL SCIENTS PUBLISHER, 2024)
The phenomenon of sleep hours on student learning achievement is a topic that needs to be discussed because the sleep hours themselves will affect the achievements achieved by students, students as one of the student component units are required to meet basic needs, namely sufficient sleep hours, To maintain human survival is required to have enough sleep hours. Basically, enough hours of sleep are needed. Sleep is a basic need needed by everyone. Everyone needs enough sleep so that the body can function normally. In the sleeping state, the body carries out a recovery process to restore the body's stamina to an optimal condition, so that he can carry out normal activities the next day. Students or students also need enough rest time to maintain the stability of their health, insufficient sleep hours will affect the learning process which of course will also affect their learning achievement as well. Learning achievement is the result of measuring and assessing students or students during the study period at an educational institution. In this study, the population we used was students of the Faculty of Communication and Multi-Media Sciences, Mercubuana University Yogyakarta Class of 2021, while the sample was fikom students themselves. This type of research is quantitative research. The instrument used in this study was a questionnaire on the influence of sleep hours and learning achievement data obtained and then analyzed using SPSS software. The results showed that the value of Sig. on deviation from linearity was 0.711 which showed that there was a linear relationship between the X variable and the Y variable. The quadratic R coefficient in the linear regression test results is 0.051 which means that 5.1% of learning achievement can be explained by students' sleep habits. So from the analysis data that has been carried out, it can be concluded that student sleep hours have an influence on the achievement of FIKOMM students at Mercu Buana University Yogyakarta.